MEDICAL DECISION-MAKING AND EDUCATION RELATED TO OSTOMY SURGERY IN PEDIATRIC PATIENTS WITH IBD: QUALITATIVE THEMES FROM MULTIDISCIPLINARY PROVIDER FOCUS GROUPS. (22nd January 2022) - David, Jennie; Dotson, Jennifer; Mackner, Laura
Abstract: INTRODUCTION: Pediatric patients with Inflammatory Bowel Disease (IBD) may undergo ostomy surgery, which surgically diverts stool to be collected in a bag worn on the abdomen. In addition to medical decision-making about ostomy surgery being innately complex and necessary to take a developmental approach, the medical decision also intersects with multiple disciplines and arguably requires nuanced coordination and collaboration for optimal medical decision-making and educational support. METHODS: Multidisciplinary providers at a large, urban pediatric institution were recruited to participate in semi-scripted focus groups on medical decision-making and education related to ostomy surgery in pediatric patients with IBD. Focus groups occurred virtually and were recorded and transcribed for qualitative analysis of focus group content, with iterative analysis to generate qualitative themes. RESULTS: Three focus groups were held, with a total of n=12 providers across all focus groups. Participants included pediatric GI providers (n=6), surgeons (n=2), GI nurse practitioner (n=1), GI social worker (n=1), and ostomy nurses (n=2). Participants reported providing care to patients at the institution for an average of 10 years (SD=9.7), and all worked with pediatric IBD patients. Focus group themes included 1) Ostomy surgery as a later treatment option for IBD patients, 2) Perception of "Defeat"/"failure, " 3) Differences between IBD patients (e.g., Crohn's Disease versus ulcerative colitis), 4) Patients feeling unwell medically pre-operatively plays a role, 5) Psychosocial needs/support of patients, 6) Professional role issues/Provider Role considerations, 7) Provider perceptions of ostomies, 8) Provider Concerns/Needs, 10) Timing Considerations/Concerns, 11) Family Considerations/Challenges, and 12) Coordination/collaboration challenges. CONCLUSIONS: The decision to consider ostomy surgery in pediatric IBD is often a complex decision that requires nuanced medical decision-making conversations and education for the patient and the parent/family. Further, this medical decision-making process often involves coordination and collaboration with multidisciplinary providers and often occurs over a period of time. This work assessed multidisciplinary providers' perception of coordination and collaboration across specialties in supporting young people with IBD considering ostomy surgery. Qualitative themes identified psychosocial needs of patients and families throughout the process, various roles of multidisciplinary providers in the ostomy surgery decision, and logistical timing and coordination concerns during this medical decision. This work highlights the developmental and psychosocial considerations in supporting patients and parents through a complex medical decision.